On a theory of network equivalence - Koetter, R.; Effros, M.; Medard, M. (2009 IEEE Information Theory Workshop on Networking and Information Theory, 2009)
We describe an equivalence result for network capacity. Roughly, our main result is as follows. Given a network of noisy, independent, memoryless links, a collection of demands can be met on the given network if and only if it can be met on another network where each noisy link is replaced by a noiseless bit pipe with throughput equal to the noisy link capacity. This result was previously known only for multicast connections.